2021
DOI: 10.3892/etm.2021.10143
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of STAT3 in neural stem cells promotes neuronal differentiation and functional recovery in rats with spinal cord injury

Abstract: STAT3 is expressed in neural stem cells (NSCs), where a number of studies have previously shown that STAT3 is involved in regulating NSC differentiation. However, the possible molecular mechanism and role of STAT3 in spinal cord injury (SCI) remain unclear. In the present study, the potential effect of STAT3 in NSCs was first investigated by using short hairpin RNA (shRNA)-mediated STAT3 knockdown in rat NSCs in vitro . Immunofluorescence of β3-tubulin and glial fibrillary acidic protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Genetic-tools have shown that ependyma-derived astrocytes have a positive effect on SCI [ 12 ] suggesting that STAT3 activation in ependymal cells is beneficial in this context. However, STAT3 acts a negative-regulator of neurogenesis in neural stem cells [ 61 , 62 , 63 ] which could be responsible for the absence of new neurons production by ependymal cells after injury. Besides differentiation and depending on their level of activation, ERK/MAPK and STAT3 pathways can also promote stem cell proliferation [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic-tools have shown that ependyma-derived astrocytes have a positive effect on SCI [ 12 ] suggesting that STAT3 activation in ependymal cells is beneficial in this context. However, STAT3 acts a negative-regulator of neurogenesis in neural stem cells [ 61 , 62 , 63 ] which could be responsible for the absence of new neurons production by ependymal cells after injury. Besides differentiation and depending on their level of activation, ERK/MAPK and STAT3 pathways can also promote stem cell proliferation [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…We propose that the inflammatory response, cellular autophagy, and the apoptotic process can control neurological impairment and recovery in tonic yang and rejuvenation soup. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Related transcription factors, miRNAs, and ECM components can be targeted to induce the neuronal differentiation of NSCs, creating abundant action sites for SCI repair. More targets for neuronal differentiation are now emerging, broadening the possibilities for SCI repair strategies ( Li et al, 2020a ; Wu et al, 2020 ; Li T. et al, 2021 ).…”
Section: Therapeutic Potential Of Nscs In Scimentioning
confidence: 99%